MAP SEMIOTICS AND THE CONCEPT OF «FIELD» IN THE ATLAS OF UNIVERSITY (Atlas of HEIs) EDUCATIONAL – MANAGERIAL TYPE - Molochko, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
Map semìotiсs formed at the junction of cartography and semiotics, linguistic science, which investigates the properties of characters and iconic systems as language structures. The importance of the consideration of its provisions for the new methods and different way of spatial analysis applications and in the used to modern techniques and methods of spatial analysis and determination of the features of the state and development of material objects, processes and phenomena and their changes in time, is conditioned by the widespread use in different areas of public activity of the object language of cartography, the requirements for which are constantly increasing. In particular, this applies to the field of science, where the concept of "field" defines the transition from "discrete to continual" in which the map semiotics provisions of cartographic modeling are essential. Examples of maps of the "fields" of density of the manifestation (spreading) of natural, social and man-made phenomena developed in different directions of scientific and practical implementation, consider the essence of the application of the normalized structure of the semiotic sides of maps content, as a reference of requirements, to justify the methodology of such research, including for institutions of the Higher Education System of Ukraine (HEIs).The work explores the possibility of using the concept of "field" in atlas mapping modeling. On the basis of this concept, the density (thickness) of the placement (spatial organization) of the structural units Taras Shevchenko National University of Kiev within the borders of Kiev is justified. Its mapping, in the form of developments of the interactive atlas of the university, local level, educational - managerial type, because of the dispersed territorial structure and thematic content of its main sections is carried out for the first time.
Keywords: cartography, map semiotics, the concept of